2019
DOI: 10.3389/fpsyg.2019.01532
|View full text |Cite
|
Sign up to set email alerts
|

Can the Attention Training Technique Reduce Stress in Students? A Controlled Study of Stress Appraisals and Meta-Worry

Abstract: The present study tested the impact of attention training on cognition; secondary appraisal of perceived stress, and on metacognition; meta-worry in stressed students. Theoretically derived from the Self-Regulatory Executive Function model (S-REF model; Wells and Matthews, 1994a , 1996 ), the attention training technique (ATT; Wells, 1990 ) is intended to promote flexible, voluntary external attention and has been shown to reduce symptoms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…To date, we are only aware of two RCT studies evaluating the effectiveness of ATT in groups. One conducted in stressed students reported a significant decrease in stress (Myhr et al, 2019 ) and another study among students reported a significant decrease in symptoms of anxiety and depression (Haukaas et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, we are only aware of two RCT studies evaluating the effectiveness of ATT in groups. One conducted in stressed students reported a significant decrease in stress (Myhr et al, 2019 ) and another study among students reported a significant decrease in symptoms of anxiety and depression (Haukaas et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, when an individual is faced with stressful situations beyond their psychological capacity, it is difficult to make effective adjustment, resulting in negative emotions such as anxiety and depression. These in turn have adverse effects on cognitive functions such as attention and hinder the completion of tasks ( Myhr et al, 2019 ). Working memory, as a cognitive resource with limited capacity, is more vulnerable to such effects ( Matthews and Campbell, 2010 ; Lukasik et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The procedure was established as the Attention Training Technique (ATT; Wells, 2000). ATT was reported to be effective in reducing depression and anxiety (Fergus et al, 2014; Knowles et al, 2016; Papageorgiou & Wells, 2000) and perceived stress (Myhr et al, 2019). However, it is unclear how selection, switching, and divided attention skills contribute to efficacy.…”
Section: Introductionmentioning
confidence: 99%